Impact of allogeneic stem cell transplantation comorbidity indexes after haplotransplant using post‐transplant cyclophosphamide. (21st September 2021) - Jullien, Maxime; Orvain, Corentin; Berceanu, Ana; Couturier, Marie‐Anne; Guillaume, Thierry; Peterlin, Pierre; Garnier, Alice; Le Bourgeois, Amandine; Klemencie, Marion; Schmidt, Aline; Hunault, Mathilde; Daguindau, Etienne; et al.
Abstract: Background: Three different scoring systems have been developed to assess pre‐transplant comorbidity in allogeneic hematopoietic stem cell transplantation (Allo‐HSCT): the Hematopoietic Cell Transplantation‐Specific Comorbidity Index, the Comorbidity/Age index, and the Augmented Comorbidity/Age index. All were devised to predict overall survival (OS) and disease‐free survival (DFS) survivals and non‐relapse mortality (NRM) in patients receiving HLA‐matched Allo‐HSCT, but their performance has scarcely been studied in the haploidentical Allo‐HSCT setting with post‐transplant cyclophosphamide, a procedure in constant expansion worldwide. Methods: To address this issue, their impact on survivals and NRM was examined in a cohort of 223 patients treated with haploidentical Allo‐HSCT in four different centers. Results: With a median follow‐up of 35.6 months, 3‐year OS, DFS, and NRM were 48.1% ± 4%, 46.3% ± 4%, and 30.0% ± 3%, respectively. No impact was found for any of the three comorbidity scores in univariate analysis. In multivariate analyses, the only three factors associated with lower OS were DRI ( p  < 0.001), an older age of recipients (≥55 years old, p  = 0.02) and of donors (≥40 years old, p  = 0.005). Older donor age was also associated with lower DFS and higher NRM. Conclusion: The comorbidity scores do not predict survivals nor NRM in haploidentical Allo‐HSCT with PTCY, suggesting that pre‐transplant comorbidities should not be a contra‐indication to this procedure. Abstract : Three different scoring systems have been developed to assess pre‐transplant comorbidity in allogeneic hematopoietic stem cell transplantation: the Hematopoietic Cell Transplantation‐Specific Comorbidity Index, the Comorbidity/Age index, and the Augmented Comorbidity/Age index, but their performance has scarcely been studied in the haploidentical stem cell transplantation setting with post‐transplant cyclophosphamide, a procedure in constant expansion worldwide. To address this issue, their impact was examined in a cohort of 223 patients from four French centers treated with haploidentical stem cell transplantation. No impact was found for any of the three comorbidity scores in this study, suggesting that pre‐transplant comorbidities should not be a contra‐indication to this procedure.